2022
DOI: 10.1007/s40257-021-00661-0
|View full text |Cite
|
Sign up to set email alerts
|

Culprit Medications and Risk Factors Associated with Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis: Population-Based Nested Case–Control Study

Abstract: Objective Our objective was to describe the incidence of Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) in a large unselected cohort, to validate the culprit drugs involved and the frequency of SJS/TEN for each drug, and to analyze the clinical risk factors for SJS/TEN. Methods Using the computerized database of Clalit Health Services, we identified all adult patients with a new SJS/TEN diagnosis between 1 January, 2008 and 30 June, 2019 and validated each case. Cumulative incidence of SJS/TEN f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…In this study, we showed that 3 underlying diseases were associated with the development of SJS/TEN, namely systemic autoimmune disease and type 2 diabetes, as previously shown, 9 and peripheral vascular disease. In autoimmune disease, disturbed regulatory immunity augments cytotoxic reactions, which are associated with the induction of SJS/TEN.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In this study, we showed that 3 underlying diseases were associated with the development of SJS/TEN, namely systemic autoimmune disease and type 2 diabetes, as previously shown, 9 and peripheral vascular disease. In autoimmune disease, disturbed regulatory immunity augments cytotoxic reactions, which are associated with the induction of SJS/TEN.…”
Section: Discussionsupporting
confidence: 77%
“…Patients with SJS/TEN were defined as those with a medical claim with the disease code, which is the code used for billing medical fees for SJS/TEN (SJS: 6951003, TEN: 8845586). In this study, the candidate risk factors were age, sex, and the presence of comorbidities using the Elixhauser comorbidity index 20 and previously reported risk factors and candidate risk factors 8 , 9 , 21 , 22 (as defined using the ICD-10, Supplementary Table I, available via Mendeley at https://data.mendeley.com/datasets/yd63zxsgxy/1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients ceased the suspected drug upon SJS/TEN diagnosis in this study [ 20 ]. Other studies found the culprit drugs that were at high risk for triggering SJS were phenytoin, lamotrigine, and allopurinol [ 21 , 22 ]. An increased risk for developing SJS is associated with factors such as age, autoimmune disease, previous drug allergies, epilepsy, or a history of cerebrovascular accident [ 23 - 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although our patient responded appropriately to MAS treatment, she was exposed to multiple medications during the early, uncontrolled phase of MAS, which may have increased her risk of developing TEN. The presence of inflammatory disorders, such as autoimmune disease, increases the risk of TEN, particularly in the early stages before the disease is controlled [ 4 ]. Inflammation promotes antigen presentation and activation of T cells and NK cells, leading to drug-specific CD8 + T cell and NK cell-mediated epidermal damage [ 5 ].…”
mentioning
confidence: 99%